About the Gibbs-Appel equations for multibody systems - Khang, Nguyen Van (Vietnam Journal of Mechanics, 2006)
In this paper a matrix form of Gibbs-Appel function is recommended for multibody dynamics formulations. The form proposed in this paper seems to be more clear and suitable for automatic generation of dynamical equations of motion. The advantages followed from the formulation proposed are illustrated through an example